Short-Term and Long Term Benefirs of Supplier-Customer Relationship - Dian Prihadyanti (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2013)
Today, business environment has become more dynamic with more demanding customers and intense market competition. To meet this, more and more firms are conducting innovation activities. Firms which are succeed to innovate tends to survive and grow to a greater extent. Innovation may come from various sources, one of them is from external side of a firm. As one of the main sources of innovation from external side, business partner which include supplier and customer have important role to the success of innovation. This paper attempts to analyzing the role of cooperation and relationship between supplier and customer firms in Indonesia’s automotive sector, in regard with the change in innovation maturity stage of those firms. Long term and short term advantages gain from the cooperation and managed relationship are also discussed. Key factors for succesful cooperation with optimum benefits are related with trust and openness culture from both parties. Further research directions are also discussed in this paper.